The relationship between international students' perceived discrimination and self-reported overall health during COVID-19: Indirect associations through positive emotions and perceived social support - Zhang, Qiyang; Xiong, Yiying; Rose Prasath, Priscilla; Byun, Sooyeon (Journal of International Students, 2023)
Since the outbreak of the COVID-19 pandemic, cases of discrimination and hate crimes against minority populations including international students have soared in the U.S. This study explores the relationship between international students’ perceived discrimination and their self-reported overall health and the role of social support and positive emotions in such relationship. In total, 203 international students studying at two U.S. universities participated in an online survey. The results indicated that (1) when international students perceive higher levels of discrimination, they experience lower levels of positive emotions and have lower levels of perceived social support; and (2) positive emotions were significantly associated with both psychological distress and physical health. Perceived social support was only significantly associated with physical health not psychological distress. We also provided meaningful implications for higher educational institutions that strive to enhance international students’ overall health.